Assessment of Awareness Regarding Hepatitis B and C among the Urban Community of Rawalpindi - Rameen Khalid, Aamna Zamurad Khan, Muhammad Ahmad Khalid, Muhammad Faez Nazir, Omaima Asif, Asif Maqsood Butt, Faizan Shahzad, Fahad Shabbir (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
OBJECTIVE: Hepatitis B and C can cause lethal liver infections leading to permanent liver tissue damage.Globally, two billion individuals have encountered the Hepatitis B virus and 100 million individuals have encountered the Hepatitis C virus.The objective of this study was to evaluate knowledge,attitudes and practices of urban community in Rawalpindi towards Hepatitis B and C. METHODS: A descriptive cross-sectional study was conducted in July 2023 among 277 participants. Data was collected through a questionnaire assessing knowledge, attitudes, and practices related to Hepatitis B and C. The responses to the questionnaire were recorded in SPSS version 25. Responses of participants were compared on the basis of both gender and educational level through Chi square test. Responses were also compared on the basis of age via Kruskal- Wallis H test. P-value<0.05 was considered statistically significant. RESULTS: Among the participants, 135 (48.7%) were male, and 142 (51.3%) were female, with a mean age of 38.13 years ±12.76 years. The majority had not received Hepatitis B vaccination (61%), and only 27.1% had undergone screening. Participants from the secondary education level demonstrated higher knowledge levels in various aspects of Hepatitis B and C. There was no significant difference between genders, except for female participants being more informed about the potential lifelong persistence of the diseases. CONCLUSION: This study provides valuable insights into the knowledge, attitudes, and practices regarding Hepatitis B and C within the urban community of Rawalpindi. The results indicate a need for enhanced vaccination coverage and screening accessibility. Tailored educational initiatives can significantly contribute to improved public health outcomes in this context. KEYWORDS: Hepatitis B, Hepatitis C, Health Knowledge, Attitudes, Practices, Urban population.